Representações mentais na performance violonística - Mendonça, Maurício de Oliveira (2015)
This research shows an overview of the mental practice used in performances by classical guitar experts in Brazil through literature review, interviews and concept aplications. A semi-structured questionnaire was used with professionals with an acclaimed career as concert players and/or post graduation advisors on performance/interpretative practices in this country aiming at analyzing in what ways the deliberate use of mental representations influences the process of preparation and realization of their performances. The hypothesis that these representations help in the expressivity has been confirmed and appear in various ways in the report of the interviewees and in literature. Evidences demonstrate that evoking emotional states, memories of events, objects or sensations as well as images associated with a musical intention can assist the performer. Some words, ideas, sensations or suggested images in these contexts can became a powerful foundation, provided that they find in the individual´s reference vocabulary and memories a compatible correspondent and its concrete means of realization.